Calculation method of gas‐pressure rising process in puffer chamber of high‐voltage SF6 circuit‐breaker: Effect of nozzle ablation vapor on gas pressure rise. Issue 2 (26th August 2020) - Sato, Motohiro; Yokomizu, Yasunobu; Horinouchi, Katsuhiko; Nakamura, Yasunori; Yoshitomo, Yuji; Shimizu, Yoshinori
Abstract: Regarding a PTFE (polytetrafluoroethylene) nozzle ablation due to arc radiation exposure in SF6 circuit‐breaker, the ablated mass of the nozzle was formulated as a function of an arc current and an internal radius of the nozzle surface considering the radiation power absorbed on the surface. Furthermore, this formulation contributed to subsequent development of calculation method for evaluating gas pressure rise process during current interruption. And, verification experiments of the calculation method were performed with a model SF6 circuit‐breaker equipped a puffer chamber. Calculation results derived from the developed calculation method showed good agreement with measured gas pressure rise process. On the basis of the verified results, a discussion was made to explain pressure rise mechanism.